Simulation of cesium -137sorption on clay minerals - Колябіна, Дарья Олександрівна; Жигір, Ольга Миколаївна (Eastern-European Journal of Enterprise Technologies, 2012)
In this work established that the exchangeable and nonexchangeable absorption of 137Cs by kaolin and bentonite occurs on three types of surface active centers. It was determined that non-exchange sorption of 137Cs in the bentonite is more effective